2008
DOI: 10.1115/1.3027498
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheting of Stainless Steel 304 Under Multiaxial Nonproportional Loading

Abstract: Multiaxial ratcheting is often simulated by use of nonlinear kinematic hardening models, while in reality materials show cyclic hardening/softening and additional hardening under nonproportional loading. The effect of isotropic hardening on ratcheting needs to be addressed in simulation. In this study, ratcheting tests are conducted on stainless steel 304 under uniaxial, torsional, and combined axial-torsional loading. The ratcheting strain is predicted based on the constitutive theory that incorporates a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
4
22
0
Order By: Relevance
“…The C-J-K model, employing this value for other loading paths B2-B5, improved the overestimation predicted earlier by the O-W model. The predicted ratcheting curves for loading paths B1 and B4 were found in good agreements with experimental data reported by Kim et al 51 The C-J-K model with the same multiaxial factor χ i showed a noticeable deviation of predicted ratcheting curves for paths B2, B3 and B5. The ratcheting of B6 sample predicted by the C-J-K showed some underestimation in consistent with what reported by Abdel-Karim.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The C-J-K model, employing this value for other loading paths B2-B5, improved the overestimation predicted earlier by the O-W model. The predicted ratcheting curves for loading paths B1 and B4 were found in good agreements with experimental data reported by Kim et al 51 The C-J-K model with the same multiaxial factor χ i showed a noticeable deviation of predicted ratcheting curves for paths B2, B3 and B5. The ratcheting of B6 sample predicted by the C-J-K showed some underestimation in consistent with what reported by Abdel-Karim.…”
Section: Methodssupporting
confidence: 88%
“…Table 1 presents ratcheting tests and loading conditions for tubular SS304 samples taken from. [49][50][51] In Fig. 3, loading path A1 corresponds to shear stress cycle applied in the presence of a constant axial stress.…”
Section: A T E R I a L S T E S T I N G A N D M U L T I A X I A L mentioning
confidence: 99%
See 1 more Smart Citation
“…However, for at least some hardening materials, upon plastic straining in one direction the measured yield surface not only translates due to kinematic hardening, but also changes its shape. This change of shape has been observed by many authors in different metals, see Theocaris and Hazell (1965), Kuwabara et al (2000), Ishikawa (1997), Ishikawa and Sasaki (1989), Khan et al (2009Khan et al ( ), 2010a, 2010b); Hu et al (2015); 2014), Wu and Yeh (1991), Wu (2003), Sung et al (2011), Kim et al (2009), Rousset (1985), Rousset and Marquis (1985), Benallal and Marquis (1987), among others. As observed in these experiments, the actual shape of the measured yield surface depends on several factors as the material itself, the amount of prestress, and the permanent plastic strain (probing strain) after which the onset of plasticity (i.e.…”
Section: Introductionsupporting
confidence: 63%
“…The effect of loading complexities on ratcheting response of materials was studied in literature. 22,[32][33][34][35][36][37][38][39][40][41][42][43] Hassan et al 38,44,45 argued the competence of hardening rules to address ratcheting response of materials undergoing complex loading spectra. The influence of loading steps and magnitude on ratcheting of a number of steel alloys was studied by Paul et al 46,47 and Kang et al 34,[48][49][50][51] Goodman 52 discussed how influential the effect of increase in mean stress at a constant stress amplitude on ratcheting magnitude in SS316 samples is.…”
Section: Introductionmentioning
confidence: 99%